2015
DOI: 10.1080/1540496x.2014.998918
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetry and Volatility of the Chinese Stock Market Caused by the “New National Ten”

Abstract: To curb the excessively rapid rise in housing prices in China, the State Council of China promulgated the New National Ten, which restrains speculative investment behavior and has a linkage effect on the stock market. In this study, we use a series of GARCH models to analyze the effect of the New National Ten on the volatility and asymmetry of the Shanghai Composite Index. Specifically, we investigate how changes in investors' expectations due to regulations affect the stock market. The result clearly illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Du [10] proposes that policy interventions increase volatility. However, after studying the volatility of the Chinese stock market caused by the "New National Ten", Tsai et al [11] find that the announcement and execution of the policy are effective in stabilizing the stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Du [10] proposes that policy interventions increase volatility. However, after studying the volatility of the Chinese stock market caused by the "New National Ten", Tsai et al [11] find that the announcement and execution of the policy are effective in stabilizing the stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ma et al [9] selected nine policy events occurring between 2000 and 2003, and found that China's stock market is significantly impacted by policy effects. Since the stock market policies have an endogenous dynamic inconsistency, some policies may cause fluctuations [10] while others may stabilize the stock market [11]. However, prior studies concentrate primarily on the responses of stock returns triggered by either monetary policies or several events.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although unsolved, the puzzles of China's stock market seem to make sense considering its features, such as over‐speculation by investors, domination by SOEs, and excessive intervention of the Government. What is more, China's stock market has been developing rapidly and thus its mechanism may change as time passes (Tsai et al ., ; Wang et al ., ). Though China is currently undergoing an economic transition, few studies offer a comprehensive understanding of what is happening in China's stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang, and Weng, [15], Wang, Tsai, and Lu, [16]; Wang, Tsai, and Li, [17]). Compared with the CCC-GARCH and BEKK-GARCH models, the DCC-GARCH model has simpler parameters and relatively distinct results.…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%